The Role of Ergonomics in Stress Management (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In the modern fast-paced world, stress significantly impacts both individual well-being and workplace efficiency. Ergonomics, the study of designing workspaces to meet users' needs, provides a practical solution to mitigate stress. This paper investigates the connection between ergonomic design and stress management, exploring how workplace factors contribute to stress and how ergonomic improvements can alleviate it. We will examine the physical and psychological effects of poor ergonomics, review strategies for reducing stress through ergonomic design, and highlight the benefits of incorporating ergonomic principles into workplace practices.